Eurocrats on the Brink. - Dayen, David (American Prospect, 2024)
The article focuses on the slow response of European policymakers to rising corporate and anti-democratic forces. It highlighting the grievances of farmers and the lack of compensation in European Union (EU) policies; the disconnect between EU regulations and their impact on competition and workers, and the criticism of the EU's regulatory approach by civil society groups and former EU bureaucrats; and the challenges of EU regulations in competition and worker welfare.